The Impact of Biochar Derived from Corncobs in Ameliorating Soil Quality of Rice Farm in Dutse, Nigeria - Amoo, Afeez Oladeji; Adamu , Suleiman Bashir; Musa , Aminu; Adeleye , Adeniyi Olarewaju; Asaju , Catherine Iyabo; Ijanu , Emmanuel Madu; Bate, Bade Garba; Amoo , Nureni Babatunde (Journal of Scientific Insights, 2024)
In response to the challenges posed by organic soil contamination, a promising approach involves the application of biochar. This study investigates the effects of biochar derived from corncobs on soil organic matter, organic carbon, and soil microbial biomass carbon through one-factor factorial design experiments. Crushed corncobs were subjected to pyrolysis at 300 °C to produce corncobs-biochar, which was incrementally added to pots containing four different levels of paddy soils. Results indicated a significant enhancement (p<0.05) in the physicochemical composition of samples and improved acid degradation upon the addition of corncob-biochar with pH increasing from 1.3 in control to 9.10 in the highest treatment (TP4), along with notable improvements in electrical conductivity, cation exchange capacity, and organic carbon levels. The most effective biochar applications, TP3 and TP4, demonstrated improved nutrient retention and reduced soil acidity. This suggests that incorporating corncob-biochar into the soil can ameliorate acidic conditions and sequester carbon for future ecosystem use. In conclusion, amending soil with corncob-biochar demonstrates a notable enhancement in soil quality. The environmentally friendly application of corncob-biochar could be recommended by offering a sustainable and economically practical strategy for enhancing soil quality, addressing soil degradation, and promoting long-term agricultural productivity.